Primer registro del género Echinomyces (Ascomycotina, Diatrypales) para la micobiota de México - Chacon, Santiago (Instituto de Ecología, A.C., 1999)
Echinomyces obesa is reported from a tropical subdeciduous forest of the state of Quintana Roo. Previously, it was only known from Africa.